Castings principles the new metallurgy of cast metals - Campbell, John, 1938-; Campbell, John, MAFS. (Burlington, Mass. : Butterworth Heinemann, 2003)
This is the key publication for professionals and students in the metallurgy and foundry field. Fully revised and expanded, Castings Second Edition covers the latest developments in the understanding of the role of the liquid metal in controlling the properties of cast materials, and indeed, of all metallic materials that have started in the cast form. Practising foundry engineers, designers, and students will find the revealing insights into the behaviour of castings essential in developing their inderstanding and practice. John Campbell OBE is a leading international figure in the castings industry, with over four decades of experience. He is the originator of the Cosworth Casting Process, the pre-eminent production process for automobile cylinder heads and blocks. He is also co-inventor of both the Baxi Casting Process (now owned by Alcoa) developed in the UK, and the newly emerging Alotech Casting Process in the USA. He is Professor of Casting Technology at the University of Birmingham, UK. * New edition of this internationally respected reference and textbook for engineers and students; * Develops understanding of the concepts and practice of casting operations; * 'Castings' is the key work on castings technology and process metallurgy, and an essential resource on contemporary developments and thinking on the new metallurgy of cast alloys; * Revised and updated throughout, with new material on subjects including surface turbulence, the new theory of entrainment defects including folded film defects, plus the latest concepts of alloy theory.
Preface; Dedication; Introduction; The melt; Entrainment; Flow; The mould; Solidification structure; Gas porosity; Solidification shrinkage; Linear contraction; Structure, defects and properties of the finished casting; Processing; Environmental interactions; References; Index.
Rev. ed. of: Castings. 1991.
Includes index.
Includes bibliographical references and index.
Keywords: Founding; Metal castings; Electronic books